Bética y el regionalismo andaluz : a popósito del centenario / [José Hurtado Sánchez, Juan Ortiz Villalba, Salvador Cruz Artacho (coords.)] - Hurtado Sánchez, JoséOrtiz Villalba, JuanCruz Artacho, Salvador
Bibliografía: p. 149-150